Case Report: Carglumic acid accelerates ammonia clearance in a neonate with methylmalonic acidemia - Ma, Qianli; Luo, Yunfeng; Zhang, Xu; Xu, Ling; Shi, Dong; Shi, Meijuan; Yu, Diao (Frontiers in Pediatrics, 2025)
Carglumic acid, an orphan drug derived from N-acetylglutamate, activates rate-limiting enzymes in the urea cycle, thereby promoting ammonia clearance and detoxification. Carglumic acid is a potent treatment option for hyperammonemia resulting from rare urea cycle disorders; however, clinical experience and data on its use in neonatal hyperammonemia remain limited. Herein, we report the case of a 10-day-old girl with hyperammonemia secondary to methylmalonic acidemia (MMA) who experienced a resurgence of plasma ammonia levels after a reduction in dialysis replacement fluid. A sharp decrease in ammonia levels was observed on the second day following the administration of carglumic acid (200 mg/kg/day) during acute management. During a long-term follow-up of 1 year with low-dose maintenance (50 mg/kg/day) therapy, her plasma ammonia levels remained within acceptable limits, accompanied by normal neurodevelopment and growth. This case highlights that carglumic acid may be a promising therapeutic option for both acute and long-term management of hyperammonemia secondary to MMA in neonates, potentially facilitating prevention of irreversible neurological damage.